Education: Optimal Choice and Efficient Policy - Wolfram F. Richter; Kerstin Schneider (Center for Economic Studies and ifo Institute (CESifo), 2015)
The research on earnings determination is based on the Mincer-Becker assumption that individuals decide on schooling by maximizing income. This paper offers an alternative and less restrictive approach based on utility maximization. Using this approach, we analyze the efficiency of education policy in Ramsey's tradition. Distortive wage taxation is shown to provide an efficiency reason for subsidizing education in effective terms. Second-best policy is confronted with empirical evidence for OECD countries.
Keywords: J24; H21; I28; 330; schooling choice and earnings functions; utility vs. earnings maximization; power law of learning; second-best taxation in Ramsey's tradition; empirical evidence